Integration Of Epistemology And Axiology In Islamic Education In The Qur’an: A Thematic Study Of Qs. Al-‘Alaq And Qs. Luqman - Siti Nurhayati; Weny Alpina; Rizka Putri Susilo Ningrum; Benny Prasetiya (Al-Hikmah: International Journal of Islamic Studies, 2026)
This study examines QS Al-‘Alaq (1–5) and QS Luqmān (12–19) to formulate the objectives of Islamic education, reinforced by the perspectives of al-Ghazālī, Ibn Sīnā, Ibn Khaldūn, and Ibn Miskawaih. Using library research and thematic analysis of Qur’anic verses, classical works, and recent studies, it identifies epistemological and axiological foundations of Islamic education. QS Al-‘Alaq establishes an epistemological basis through the command iqra’, affirming Allah as the ultimate source of knowledge and encouraging intellectual and literacy development. QS Luqmān provides an axiological framework emphasizing wisdom, moral character, social responsibility, and ethical guidance. Classical scholars further strengthen this integration: al-Ghazālī stresses purification of the soul and unity of knowledge and action; Ibn Sīnā highlights holistic human development; Ibn Khaldūn underscores social formation; and Ibn Miskawaih focuses on moral training. The study concludes that Islamic education must adopt an integrative approach uniting spiritual, intellectual, moral, and social dimensions to form faithful, knowledgeable, and virtuous individuals.